REALIZATION OF THE INTERNATIONAL LABOR STANDARDS AT THE ENTERPRISES OF THE FREE PORT OF VLADIVOSTOK: WILL THE INVESTORS SAY THE LAST WORD? - Gorian, Ella; Litvinova, Svetlana (PEOPLE: International Journal of Social Sciences, 2017)
The special legal regime of the free port of Vladivostok simplifies the attraction of foreign labor force to enterprises. The current legislation of the Russian Federation does not fully guarantee the rights of such workers who have the status of labor migrants, since the current international standards for the protection of their rights are not ratified by the Russian Federation, nor are international standards for protecting the rights of indigenous peoples. The aim of this work is to analyze the issues of ensuring international labor standards at the enterprises of the free port of Vladivostok and to consider the theoretical aspects of this problem. In order to obtain the most reliable scientific results, a number of general scientific (system-structural, formal-logical and hermeneutical methods) and special legal methods of cognition (comparative legal and formal-legal methods) were used in complex. The results of the study are provisions on the need to include residents of the free port of Vladivostok in the system of shared responsibility of participants in the global supply chain and using one of the available models: a model of individual responsibility or a model of shared responsibility of companies to employees in the enterprise. The obtained results can be used for qualitative improvements of institutional and regulatory and socio-economic conditions for the development of the Far East, as well as for certain zones with a special economic regime of functioning. The author came to conclusions about the difficulties that exist in the way of ratification and further implementation of international labor standards: corruption, imperfect legal and institutional mechanisms, the lack of political will to resolve problems. The author sees the solution to the existing problems in the active participation of resident companies in securing the rights of workers in their enterprises located in special economic zones.